Dynamic Pedagogy for Critical Thinking: A Narrative Inquiry in Digital EFL Reading - Henny Iswati; Ahmad Munir; Him’mawan Adi Nugroho (International Journal of Pedagogical Language, Literature, and Cultural Studies (i-Plural), 2025)
This study aimed to capture the dynamic pedagogy of two Indonesian EFL lecturers to scaffold students’ critical thinking in digital reading. Driven by Clandinin’s (2000) narrative inquiry model, this study employed semi-structured interviews to investigate the development of teaching practices, student engagement with digital technology, and the promotion of dialogic teaching processes. This study found through thematic analysis that there were three main components of dynamic pedagogy: (a) Temporal scaffolding, namely, developing critical thinking via sequenced tasks designed to increase task difficulty progressively; (b) Mediating spaces, namely, creating critical spaces through digital media, including online platforms such as Google Docs and Padlet; and (c) Relational feedback - developing critical thinking via dialogic interaction to promote metacognitive thinking. Although uneven digital expertise and institutional support were difficult, the participants were flexible and shaped their pedagogy to account for the (critical) literacy demands of the students. This research contributes to the literature on EFL digital pedagogy by highlighting the teacher’s role in facilitating critical thinking as an ongoing, complex, and contextually bound process. There are also pedagogical implications, such as integrating digital skills instruction, providing iterative feedback to students on their digital sources (both online and offline), and offering professional development in digital critical literacy pedagogy.